1998
DOI: 10.1063/1.477776
|View full text |Cite
|
Sign up to set email alerts
|

State-specific vibrational anharmonicities in cyclobutadiene and evidence for fast automerization by C412H4

Abstract: MO computations of vibrational spectra for 1,3-cyclobutadiene (CB) and CB:CO2 van der Waals molecule isotopomers at the MP2/6-311++G(2d,2p) level of MO theory are analyzed together with the extensive Ar/CB matrix-isolation spectra of the Michl group, the low 3.2 kcal/mol (ZPE-corrected) MO-computed energy of the square-planar saddle-point for CB reported by Nakamura et al., and opportune one-dimensional analysis of the automerization energy levels of C412H4. The composite interpretation results in the assignme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Subsequent, more sophisticated, calculations on the automerization of CBD‐d 2 and experiments by Michl and coworkers on the isomerization of CBD‐1,2‐ 13 C 2 in matrix isolation, confirmed Carpenter's conclusions about the important role that tunneling by carbon plays in the CBD automerization reaction.…”
Section: Three Early Examples Of Tunneling By Carbonmentioning
confidence: 68%
“…Subsequent, more sophisticated, calculations on the automerization of CBD‐d 2 and experiments by Michl and coworkers on the isomerization of CBD‐1,2‐ 13 C 2 in matrix isolation, confirmed Carpenter's conclusions about the important role that tunneling by carbon plays in the CBD automerization reaction.…”
Section: Three Early Examples Of Tunneling By Carbonmentioning
confidence: 68%
“…Large kinetic isotope effects (KIEs) in hydrogen transfer reactions have often been interpreted as a diagnostic for tunneling through the reaction barrier. 1,2 The extent of tunneling is mass dependent and decreases with increasing mass of the atom. The much larger mass of carbon decreases its tunneling probability and consequently the effect of carbon tunneling on reaction rates is often ignored.…”
mentioning
confidence: 99%
“…As a result, carbon tunneling is much less understood and has been addressed for only a handful of chemical reactions. 2 It has been observed that allowance for tunneling improves the prediction of heavy-atom isotope effects, but tunneling corrections in most reactions not involving hydrogen transfer are very small. As a result, heavy-atom KIE predictions based solely on TST, not allowing for tunneling, are still usually reasonably accurate 3 and sufficient for mechanistic interpretation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two bands around 760 and 1640 cm 21 are not been predicted by CASSCF. These vibrational modes are related to the automerization transition, 45 and therefore, they cannot be calculated with the harmonic approximation. In a recent publication, 46 these bands have been calculated using the present CASSCF calculations and an anharmonic model, confirming that the transformed product can be identified as TMCBD.…”
Section: Characterization Of the Energy Barriers And Minimamentioning
confidence: 99%